Kewenangan Penyelenggaraan dan Pertanggungjawaban Ibu Kota Negara Berdasarkan Uud No. 3 Tahun 2022 Tentang Ibu Kota Negara - Ihza Mahendra, Yusril; Harvelian, Agnes; Mulyana, Momon (Postulat, 2025)
The relocation of Indonesia’s new capital city (IKN) demands significant funding, raising concerns about inefficiency in the State Budget (APBN) and issues in the drafting of Law Number 3 of 2022 on the State Capital. This study analyzes the authority and accountability of the Nusantara Capital City Authority within Indonesia’s constitutional system. Using a normative juridical method, the research finds that Article 12 paragraph (1) of Law No. 3/2022 grants the Authority the status of a special regional government, distinguishing it from general regional administrations. Furthermore, Article 13 specifies that elections in IKN are limited to the President and Vice President, DPR, and DPD members, with no local elections or DPRD. This centralized appointment of the Head of the Authority by the President challenges democratic values and decentralization principles. Therefore, transparent selection, strong oversight, and balanced investment policies are crucial to ensure accountable governance that safeguards national interests.